2010
DOI: 10.1007/s12098-010-0355-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Dilemma of JMML Coexisting with CMV Infection

Abstract: Juvenile myelomonocytic leukemia (JMML) is a rare mixed myeloproliferative and myelodysplastic disorder of early childhood, characterized by excessive proliferation of monocytic and granulocytic cells, along with myelodysplastic features. There are reports of viral infections mimicking JMML, with all clinical and hematological parameters normalizing on resolution of infection. The authors describe a 1- year- old boy with concomitant JMML and CMV infection. The diagnostic dilemma, the significance of distinguis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…3 However, as this assay could test positive in certain viral infections, it is considered a sensitive but non-specific assay. 11 Moreover, differentiation between CMV-related disease and JMML in infants excreting CMV is sometimes difficult, 22, 23, 24 because clinical and laboratory findings of CMV infection can overlap with those of JMML. 11 …”
Section: Discussionmentioning
confidence: 99%
“…3 However, as this assay could test positive in certain viral infections, it is considered a sensitive but non-specific assay. 11 Moreover, differentiation between CMV-related disease and JMML in infants excreting CMV is sometimes difficult, 22, 23, 24 because clinical and laboratory findings of CMV infection can overlap with those of JMML. 11 …”
Section: Discussionmentioning
confidence: 99%
“…Estimates have shown that approximately 20 cases of JMML occur annually in Japan, with the median age at diagnosis being 2 years (2). A suspected case of JMML typically presents with non-specific constitutional signs and symptoms, such as fever, infection, pallor, bleeding, cough, poor weight gain, maculopapular rash, lymphadenopathy, moderate hepatomegaly, marked splenomegaly, leukocytosis, absolute monocytosis, anemia, and thrombocytopenia (3).…”
Section: Introductionmentioning
confidence: 99%
“…However, survival up to 57-64 % have been reported post allogeneic stem cell transplant (SCT) [5,6]. There is a paucity of outcome data for JMML from India [7][8][9].…”
Section: Introductionmentioning
confidence: 99%